Analisis Faktor–Faktor yang Mempengaruhi Kepuasan Konsumen Terhadap Layanan Internet pada Warnet - Purba, Elvitrianim (Journal of Management and Economics Research, 2023)
Nowadays, competition in the business world is becoming increasingly fierce. Including business competition in the business sector providing internet services. Warnet Power Comp is one of the service companies operating in this business field. Even though it has many competitors from the same field, the Amanah net cafe, which is also one of the pioneers of internet cafes in the Rantauprapat area, is still able to survive by implementing various strategies. This research was conducted based on the fact that there is a lot of interest from the public, especially students who need internet services in everyday life. The large number of internet service businesses that are booming in the Sragen area means that consumers can compare the quality of service offered by internet service businesses to satisfy customers. This research itself aims to determine the extent of consumer satisfaction with the services provided by Amanah net based on four product attribute dimensions, namely internet speed/bandwidth (X1), features (X2), price tariff (X3) and service quality (X4) on satisfaction (Y) at Amanah net Sragen internet cafe. The sample for this research was 100 respondents, using an accidental sampling method with a population of all Power Comp internet cafe consumers. The analytical method used in this research is descriptive statistical analysis which is an interpretation of the data obtained in the research as well as the results of data processing that has been carried out by providing information and explanations. Apart from that, quantitative analysis using the regression analysis method is also used, the testing stages are validity, reliability, classical assumptions, multiple linear regression analysis, hypothesis testing and coefficient of determination. Based on the calculation results of the SPSS version 16.00 computer program, the following results were obtained: Y = 1.653 + 0.250 X1 + 0.248X2 + 0.218 service to the satisfaction of Power Comp Rantauprapat internet consumers "is proven to be true", proven by the calculation results which obtained an Fcount value of 26.174, this number means that Fcount is greater than Ftable so the decision is to reject Ho. Thus, simultaneously the variables of speed/bandwidth, cleanliness and facilities, price rates and service quality significantly influence Internet Power Comp Rantauprapat consumer satisfaction. Internet speed/bandwidth has the most dominant influence on Internet consumer satisfaction. Power Comp Rantauprapat "is proven to be true", proven by the calculation results which obtained a regression coefficient value of 0.250